Analisis Evaluasi Kewajaran Harga terhadap Kualitas Pekerjaan Pembangunan Jembatan Log Cs - Antonius Suranta Peranginangin; Dewi Ana Rusim; Mujiati Surianata (Fakultas Teknik Universitas Cenderawasih, 2024)
Tender offer below 80% HPS can cause concerns during the implementation of the work, including the quality of work that does not meet the standards in the contract, delays to contract termination. The purpose of this study is to analyze the evaluation of price reasonableness, time performance, quality performance and describe the quality of work. The research variable is Quality of Work (X). The research method used is Quantitative Descriptive Analysis using SPSS version 26. Data collection methods using interviews and questionnaires. The analysis used is Price Fairness Evaluation Analysis, Time Performance Analysis, Quality Performance Analysis, and Quantitative Descriptive Analysis. The results of the fairness evaluation analysis show that the total bid without VAT is more than the total clarification price so that the bid is declared reasonable. Time Performance Analysis shows the acceleration of the project against the plan, Quality Performance is more than the quality of the plan. Descriptive Analysis of the quality of the Log Cs Bridge Construction work is Good. The price quote of PT Tantu Konstruksi Engineering is declared reasonable. Time Performance is Good, Quality Performance is Good. The quality of work on the construction of the Log Cs Bridge is good.